Near-peer tutoring: An effective adjunct for virtual anatomy learning - Sioufi, Jeffrey; Hall, Brandon; Antel, Ryan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Implication statement With recent shifts in medical education to the virtual setting during the COVID-19 pandemic, previous methods of teaching anatomy have been challenged. As such, we created the Medical Students’ Society Anatomy Club (MAC), a student-led near-peer tutoring initiative providing virtual anatomy learning opportunities through interactive large and small group sessions using cadaveric prosection images and models. Sessions had high attendance rates and satisfaction among students. This pilot project demonstrated that near-peer teaching in a virtual learning environment can be an effective adjunct to traditional medical anatomy curricula.